Electrical and physical studies of polymer electrolyte based on methylgrafted natural rubber (MG30) / Nur Hamizah Mohd Zaki - Mohd Zaki, Nur Hamizah (2014)
This dissertation focuses on the preparation and characterization of MGS 0-salt complexes and plasticized MG30-salt complexes. In the present study, 30% poly(methylmethacrylate) grafted natural rubber (MG30) as polymer host, ammonium trifluoromethanesulfonate (NH4CF3SO3) as doping salt and ethylene carbonate (EC) as plasticizer were used in the preparation of solid polymer electrolytes (SPEs) and gel polymer electrolytes (GPEs). The SPEs and GPEs were prepared by the solution cast technique with different weight percent (wt.%) of NH4CF3SO3 and EC. The conductivity of the samples were characterized by the impedance spectroscopy in the frequency range between lOOHz and IMHz. Highest ionic conductivity of SPE containing 35 wt.% NH4CF3SO3 in MG30:NH4Cp3S03 was 1.94x10"^ Scm"’. Further enhancement of ionic conductivity obtained with addition of plasticizer into SPE was 9.61x10-'^ Scm-' at the composition of 26:14:60 wt.% for MG30:NH4CF3S03:EC. ATR-FTIR spectroscopy justify the interactions between polymer and salt primarily due to the C=0 of MG30 and NH4^ of salt. The shifting of the carbonyl peak C=0 of MG30 at 1728cm"' to the lower wavenumber indicates coordination takes place between ammonium cation and C=0 to form NH4^<—0=C interaction. FTIR studies also confirm the addition of plasticizer just penetrated in between polymeric chain and create more free volume by reducing the polymer chain cross linking without perturbing the complexation of polymer-salt. XRD analysis confirmed the formation of polymer-salt complexes with the decreasing of peak intensity at 20=44.3° and 55.6° of MG30 upon the addition of salt and plasticizer content. Besides that, XRD spectra analysis demonstrated the incorporation of plasticizer has reduced the crystallinity of MG3O-NH4CF3SO3 promotes to ion migration easily hence lead to the ionic conductivity enhancement. The differential scanning calorimetry (DSC) analysis found the introduction of EC into SPE has decreased the Tg value suggesting that EC have disturbed the crystalline domain of polymer thus reduced the degree of crystallinity of the polymer electrolytes. The energy band gap (Eg) foimd to decrease with increasing of plasticizer and salt content by UV-Visible studies. The dopant (salt and plasticizer) considered as defect in polymer which affects the optical band gap.The window stability of SPE was observed around 2.2V whereas the window stability of GPE was around 2.7V.